Genome Sequence and Metabolic Analysis of a Fluoranthene-Degrading Strain Pseudomonas aeruginosa DN1 - He, Chunqiu; Li, Yanpeng; Huang, Chao; Chen, Fulin; Ma, Yanling (Frontiers in Microbiology, 2018)
.Pseudomonas aeruginosa DN1, isolated from petroleum-contaminated soil, showed excellent degradation ability towards diverse polycyclic aromatic hydrocarbons (PAHs). Many studies have been done to improve its degradation ability. However, the molecular mechanisms of PAHs degradation in DN1 strain are unclear. In this study, the whole genome of DN1 strain was sequenced and analyzed. Its genome contains 6,641,902 bp and encodes 6,684 putative open reading frames (ORFs), which has the largest genome in almost all the comparative Pseudomonas strains. Results of gene annotation showed that this strain harbored over 100 candidate genes involved in PAHs degradation, including those encoding 25 dioxygenases, four ring-hydroxylating dioxygenases, five ring-cleaving dioxygenases, and various catabolic enzymes, transcriptional regulators, and transporters in the degradation pathways. In addition, gene knockout experiments revealed that the disruption of some key PAHs degradation genes in DN1 strain, such as catA, pcaG, pcaH, and rhdA, did not completely inhibit fluoranthene degradation, even though their degradative rate reduced to some extent. Three intermediate metabolites, including 9-hydroxyfluorene, 1-acenaphthenone and 1, 8-naphthalic anhydride, were identified as the dominating intermediates in presence of 50 g/mL fluoranthene as the sole carbon source according to gas chromatography mass spectrometry analysis. Taken together, the genomic and metabolic analysis indicated that the fluoranthene degradation by DN1 strain was initiated by dioxygenation at the C-1, 2-, C-2, 3-, and C-7, 8- positions. These results provide new insights into the genomic plasticity and environmental adaptation of DN1 strain.